PENERAPAN METODE PEMBELAJARAN INQUIRY TERBIMBIBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKAN SISWA KELAS XI SMKN 3 MATARAM TAHUN PELAJARAN 2024/2025 - Nurhawiajah; Sutarto; Yuliyanti, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is the lack of interest in learning that has an impact on the learning outcomes of class XI TKP SMK 3 Mataram students on the Circle material. To overcome this problem, the researcher used the Inquiry learning method with the aim of increasing the interest and learning outcomes of class XI TKP SMK 3 Mataram students. This study uses a quantitative approach with the type of classroom action research (PTK). The data sources used were 25 students from class XI TKP SMK 3 Mataram. Data collection procedures include distributing questionnaires and learning outcome tests. The results of the study showed: (1) The average value of learning outcomes in cycles I and II was 41.2 and 84, while the percentage of completion in cycles I and II was 12% and 85.6% with very low and very high criteria. (2) The average interest in learning in cycle I was 39.09 with fairly good criteria. Thus, the results of this study indicate that the application of the Inquiry learning model to the Circle material can increase student interest and learning outcomes.